2000
DOI: 10.1002/(sici)1097-4628(20000725)77:4<792::aid-app11>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on mechanical-electrical behavior of graphite powder-filled high-density polyethylene composites

Abstract: Mechanical and electrical responses of graphite powder (GP)-filled highdensity polyethylene composites to a uniaxial compression-decompression cycle were studied. Above a compression loading level, a large positive-pressure coefficient effect of resistance was observed, for which a slide mechanism of GP in the matrix is believed to be responsible. In a step-wise compressive loading and loading-holding experiment, the critical compression level was also found, at which the resistance response changed from a tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Graphite flake can also enhance mechanical properties, corrosion resistance and lighten the weight of materials [1][2][3][4]. To meet satisfactory conductivity, the loadings of conventional graphite flake filler particles with micrometer scale are often up to 20 wt%, which is not beneficial to improve the mechanical properties and reduce the density of materials.…”
supporting
confidence: 78%
“…Graphite flake can also enhance mechanical properties, corrosion resistance and lighten the weight of materials [1][2][3][4]. To meet satisfactory conductivity, the loadings of conventional graphite flake filler particles with micrometer scale are often up to 20 wt%, which is not beneficial to improve the mechanical properties and reduce the density of materials.…”
supporting
confidence: 78%
“…When the nanoscale graphene distributed in c-GNLC composite host, the current density ( J ) in the composite formed by two c-GNLC platelets with a small distance ( d ) at low voltage ( U ) can be determined by the following equality: where m is the electron mass, e is the charge, h and j are the Planck constant and the barrier height between two adjoining c-GNLC platelets, respectively. R m represents the resistance of a composite and n and a 2 represent the effective cross-section area and a total number of such junctions, respectively; the resistance of a composite is obtained as When the distance between the adjacent c-GNLC platelets is reduced from the initial d 0 to the intermediate level ( d ) in the load period, the resistance of c-GNLC composite ( R m ) changes from R 0 to R at the same time, then the relative resistance ( R / R 0 ) is obtained as where d 0 is determined by the fabrication process, under uniaxial compression, the distance of adjacent c-GNLC platelets depending on external strain.…”
Section: Resultsmentioning
confidence: 99%
“…Although several investigations have been carried out in the past to relate the electrical behavior of carbon black to static and dynamic stretching,16, 17 or to hydrostatic and uniaxial compression,18–21 much less attention has been paid to studying the pressure‐dependence of nanocomposite resistance. Recently, we have prepared HDPE/FG nanocomposites and found that these materials have strong piezo‐resistive effects, which are induced by shear‐induced orientation of FG in the HDPE matrix 22.…”
Section: Introductionmentioning
confidence: 99%